Introducing Greek Philosophy. - Wright, Rosemary (Taylor and Francis, 2014)
Aimed at students of classics and of philosophy who would like a taste of the subject before being committed to a full course and at those who have already started and need to find their bearings in what may seem at first a complex maze of names and schools, ""Introducing Greek Philosophy"" is a concise, lively, philosophically aware introduction to ancient Greek philosophy. The book begins with the Milesians in Asia Minor before moving over to the developments in the western Greek world, then focusing on Socrates, Plato and Aristotle in Athens, finishing with the Hellenistic schools and their.